2015
DOI: 10.1016/j.indcrop.2014.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Modified tannin extracted from black wattle tree as an environmentally friendly antifouling pigment

Abstract: The use of modified black wattle tannin as antifouling pigment is reported in this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Adsorption studies have shown that materials such as activated carbon, phosphate and natural phosphate have been applied for the removal of heavy metals from wastewater on a commercial scale, but these adsorbents have been certified to have limited application for the removal of Pb , asbestos, cysts, and coliform [10][11][12], hence the non-application of these adsorbents as a primary filter in water treatment. Recent studies have shown that heavy metals can be removed from water and wastewater by efficient, low-cost remediation plant materials and natural tannin adsorbent [13][14][15]. Zhao et al [16] and Binaeian et al [17] reported that fabricated tannin-based dithiocarbamate and hexagonal mesoporous silicate biosorbents are efficient in the removal of Ni and anionic dye from aqueous solutions, respectively.…”
Section: Sequential Extraction Of Tanninmentioning
confidence: 99%
“…Adsorption studies have shown that materials such as activated carbon, phosphate and natural phosphate have been applied for the removal of heavy metals from wastewater on a commercial scale, but these adsorbents have been certified to have limited application for the removal of Pb , asbestos, cysts, and coliform [10][11][12], hence the non-application of these adsorbents as a primary filter in water treatment. Recent studies have shown that heavy metals can be removed from water and wastewater by efficient, low-cost remediation plant materials and natural tannin adsorbent [13][14][15]. Zhao et al [16] and Binaeian et al [17] reported that fabricated tannin-based dithiocarbamate and hexagonal mesoporous silicate biosorbents are efficient in the removal of Ni and anionic dye from aqueous solutions, respectively.…”
Section: Sequential Extraction Of Tanninmentioning
confidence: 99%
“…A. mearnsii bark tannin has a great potential to be used as a green inhibitor not only due its antioxidant properties but also because it comes from a renewable source and is already industrially produced in large scale. This tannin is condensed tannin and this group of compounds has a diversity of structures, being formed by flavonoid units . Peres et al applied A. mearnsii tannin as a corrosion inhibitor for carbon steel reaching efficiencies up to 97%, and they observed that its efficiency depends on tannin concentration and that it was more effective as inhibitor in acidic medium.…”
Section: Introductionmentioning
confidence: 99%
“…The Figures on the COM sample are supplied in our previous study (both studies were carried out at same time) [69]. The COM [69] still did not present any heavy fouling after 7 months of immersion.…”
Section: Immersion Testsmentioning
confidence: 93%